Further biembeddings of twofold triple systems - Donovan, Diane M. (Ars mathematica contemporanea, 2015)
We construct face two-colourable triangulations of the graph ?$2K_n$? in an orientable surface; equivalently biembeddings of two twofold triple systems of order ?$n$?, for all ?$n \equiv 16$? or 28 (mod 48). The biembeddings come from index 1 current graphs lifted under a group ?$\mathbb{Z}_{n /4} × \mathbb{K}_4$?.
Keywords: biembedding; dvojne vložitve; dvojni sistemi trojic; orientabilne ploskve; orientable surface; twofold triple system